Templates as Shadow Masks to Tune the Magnetic Anisotropy in Nanostructured CoCrPt/Ti Bilayer Films. Issue 7 (31st March 2015) - Navas, David; Bi, Lei; Adeyeye, Adekunle O.; Ross, Caroline A.
<x xml:space="preserve">Abstract</x> Off‐axis deposition of Ti and CoCrPt films onto lithographically patterned templates has been used to make nanostructures with a lateral thickness variation that allows the tuning of the magnetic anisotropy. CoCrPt rectangles of 1 μm × 725 nm without a thickness variation show an out‐of‐plane easy axis and a single‐domain configuration after demagnetization. On the other hand, rectangles with a thickness variation along their longer dimension show an out‐of‐plane multidomain state, but an in‐plane vortex configuration occurs when the thickness variation is along the shorter dimension. The evolution of the magnetic behavior is understood from the change in both Ti and CoCrPt thicknesses and their effects on the magnetic anisotropy, and provides a simple method for controlling the magnetic state and reversal process of patterned nanostructures.